Enhancing Early Childhood Education Outcomes through a Parental Involvement Program: A Community-Based Participatory Action Research in an Underserved Urban Community - Monica Roito Ambarita; Rulik Endarwati; Muh. Safar; Ridayani Ridayani; Muhammad Syahrul (International Journal of Community Service (IJCS), 2026)
Parental involvement is a critical determinant of early childhood education (ECE) outcomes, yet it remains persistently low in underserved urban communities in Indonesia due to socioeconomic pressures, low parental self-efficacy, and fragmented school-community linkages. This study employed a qualitative community-based participatory action research (PAR) design to co-develop, implement, and evaluate a culturally grounded parental involvement program in a densely populated, low-income neighborhood in North Jakarta. Over eight months, 32 parents, 4 ECE teachers, and 2 community facilitators engaged in three iterative cycles of planning, action, observation, and reflection. Data were gathered through participant observation, in-depth interviews, focus group discussions, and reflective journals, and analyzed using thematic analysis. The PAR process catalyzed four interconnected outcomes: heightened parental self-efficacy, richer home learning environments, improved parent-teacher communication, and the emergence of informal community support networks. A pre-post involvement checklist corroborated qualitative shifts, showing marked increases in all involvement indicators. The findings suggest that a participatory, asset-based approach can transform parental involvement from a prescriptive school demand into a shared community practice, thereby strengthening ECE outcomes in marginalized urban settings. The study offers a replicable model for fostering sustainable family-community-school partnerships in similar resource-constrained contexts.